ANALISIS KEBUTUHAN PENGEMBANGAN MULTIMEDIA INTERAKTIF BERBASIS ANDROID UNTUK MAHASISWA TEKNOLOGI LABORATORIUM MEDIS - anggun sophia (LLDIKTI Wilayah X, 2019)
This study aims to determine the learning problems in molecular biology. This type of research is descriptive quantitative research. Methods of data collection was conducted by interviewing professor of molecular biology and distributing questionnaires to students who have been through the eyes of molecular biology. Results of the study are students experiencing difficulty in studying the molecular biology of material because the material is abstract and limitations of using instructional media used, for it takes the android-based multimedia interactive learning can help students in learning.